Representação temática da informação: reflexões sobre a prática da indexação do prontuário do paciente - Rabelo, Camila Regina de Oliveira (2019)
The main objective of this research is to investigate how the studies on Information Thematic Representation can contribute to indexing with use of the patient's medical record codification in the hospital environment. The patient‟s medical record is the main record document of information in the Health area presenting data related to the health and illness conditions of a person, as well as about his creed and some of his physical characteristics and social conditions. The state of the art, which is the theoretical base of this study, was based on specialized literature related to the areas of Information Science and Health Sciences, particularly the cognitive schemas of thematic representation of information. The research has a qualitative and exploratory approach by which there is a relationship between the thematic representation of information, investigated in the field of Library Science and Information Science, and the codification of the patient's medical record, a practice happening in the health area by using the ICD-10 document language. The research foundation method is one based on functionalism in order to understand the role of the particular social use of medical records‟ indexing. It is an exploratory research that proposes the guidelines for the conduction of the patient‟s medical record indexing, considering the logical and physical structure of this document. After approval by the Research Ethics Committee of the Federal University of Ceará via “Plataforma” Brasil”, the research was carried out at the Medical and Statistical Archive Service (SAME) of the Walter Cantídio University Hospital of the Federal University of Ceará (UFC). We selected and made available a set of eight patient‟s medical records with larger and full content in relation to the number of times they received care. These records were chosen according to the guidelines of the institution and after the first analysis we chose three. A total of 1,212 pages of medical records were analyzed. The results indicate that the steps of indexing can help in the understanding of the medical record as a very particular document, by using the texts recorded in the summaries of discharge for the extraction of metadata, considering the thematic representation, that can be used to retrieve the information. In addition, results show that there are similarities between the thematic representation of information and the codification practice with ICD-10, and that the techniques used in indexing can help in the representation and retrieval of information in the medical record. We conclude that the patient's medical record codification is similar to the thematic representation of the information, since it is based on analysis and translation, by using a strict quality control.